Seed Moisture Isotherms, Sorption Models, and Longevity - Hay, Fiona R.; Rezaei, Shabnam; Buitink, Julia (Frontiers in Plant Science, 2022)
Seed moisture sorption isotherms show the equilibrium relationship between water content and equilibrium relative humidity (eRH) when seeds are either losing water from a hydrated state (desorption isotherm) or gaining water from a dry state (adsorption isotherm). They have been used in food science to predict the stability of different products and to optimize drying and/or processing. Isotherms have also been applied to understand the physiological processes occurring in viable seeds and how sorption properties differ in relation to, for example, developmental maturity, degree of desiccation tolerance, or dormancy status. In this review, we describe how sorption isotherms can help us understand how the longevity of viable seeds depends upon how they are dried and the conditions under which they are stored. We describe different ways in which isotherms can be determined, how the data are modelled using various theoretical and non-theoretical equations, and how they can be interpreted in relation to storage stability.